Management of Teachers' Pedagogical Competence in Enhancing the Quality of Learning at Majelis Taklim Konversi Diniyah (MTKD) in Bandung City - Andrias Nurkamil; Endang Komara; Nana Herdiana Abdurrahman; Supyan Sauri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study is motivated by challenges in managing teacher competence to improve the quality of learning at Majelis Taklim Konversi Diniyah (MTKD). These challenges are evident in the suboptimal implementation of ensuring teachers’ mastery of pedagogical competence, which impacts graduate quality and the effectiveness of the learning process. The purpose of this research is to examine, interpret, and describe the planning, organizing, implementation, supervision, emerging issues, and solutions in managing teacher competence to enhance learning quality. The study adopts a qualitative approach and a case study method. Data collection techniques include interviews, observations, and document analysis. The findings of the study demonstrate a positive impact of teacher competence management on improving the quality of learning at MTKD. Planning is conducted collaboratively and documented in materials aligned with the learning standards of MTKD, tailored to the institution's managerial needs. Organizing is systematically structured into MTKD programs, covering the establishment of study groups (rombel), the management of participants (jamaah), and detailed budgeting. Implementation encompasses capacity building for MTKD leaders, curriculum application, and professional training and mentoring. Evaluation is carried out through direct and indirect supervision. No significant issues were identified; however, technical problems related to teaching staff resources, budgeting, and the alignment of teacher competence management with the specific situational needs of MTKD were noted. Recommendations include enhancing teacher competence, adjusting the curriculum to meet the needs of MTKD, and utilizing technology for guidance, monitoring, and professional training.